GE_GERICHTE P/6541/2024 vom 9. April 2025 - GE Cour de justice (2025)
DÉPENS;ORDONNANCE DE CLASSEMENT;INDEMNITÉ(EN GÉNÉRAL);DOMMAGE PATRIMONIAL;TORT MORAL;PREUVE;COMPLEXITÉ DE LA PROCÉDURE | CPP.429.al1.leta; CPP.429.al1.letb; CPP.429.al1.letc